2005
DOI: 10.1074/jbc.m509990200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Preprotein Binding Domain of SecA

Abstract: SecA, the preprotein translocase ATPase, has a helicase DEAD motor. To catalyze protein translocation, SecA possesses two additional flexible domains absent from other helicases. Here we demonstrate that one of these "specificity domains" is a preprotein binding domain (PBD). PBD is essential for viability and protein translocation. PBD mutations do not abrogate the basal enzymatic properties of SecA (nucleotide binding and hydrolysis), nor do they prevent SecA binding to the SecYEG protein conducting channel.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
91
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 56 publications
(117 reference statements)
4
91
0
Order By: Relevance
“…Using fragments, deletional analysis, and chemical crosslinking of synthetic signal peptides, Economou's group concluded that the region at the base of the PPXD (so-called stem region) serves to bind the signal sequence. 69,89 Results of a FRET-based study with complementary crosslinking approaches also implicated the PPXD (specifically the third Using Signal Peptides to Explore Protein Export 315 helix) in signal sequence binding, 93,95 which is consistent with the early crosslinking studies from Mizushima's lab. 94 We have performed a sequence alignment of 550 SecA proteins, and the region proposed by Musial-Siwek et al 93 has a low conservation score (J. L. Maki and L. M. Gierasch, unpublished observations), raising doubt about whether it serves as a direct binding site for signal sequences.…”
Section: Seca-signal Sequence Recognitionsupporting
confidence: 62%
See 3 more Smart Citations
“…Using fragments, deletional analysis, and chemical crosslinking of synthetic signal peptides, Economou's group concluded that the region at the base of the PPXD (so-called stem region) serves to bind the signal sequence. 69,89 Results of a FRET-based study with complementary crosslinking approaches also implicated the PPXD (specifically the third Using Signal Peptides to Explore Protein Export 315 helix) in signal sequence binding, 93,95 which is consistent with the early crosslinking studies from Mizushima's lab. 94 We have performed a sequence alignment of 550 SecA proteins, and the region proposed by Musial-Siwek et al 93 has a low conservation score (J. L. Maki and L. M. Gierasch, unpublished observations), raising doubt about whether it serves as a direct binding site for signal sequences.…”
Section: Seca-signal Sequence Recognitionsupporting
confidence: 62%
“…69 The PPXD is implicated in binding to open SecA by the finding that signal peptides stabilize an isolated construct corresponding to the PPXD in a distinct conformation. 89 As expected for a complex interplay of ligand-modulated conformational transitions, the binding of signal peptides shifts the closed to open equilibrium in SecA and modulates its ATPase activity. The addition of signal peptide to SecA in solution and in phospholipids/liposomes causes a change in SecA fluorescence 79,96 as well as in protease sensitivity.…”
Section: Seca-signal Sequence Recognitionmentioning
confidence: 98%
See 2 more Smart Citations
“…The cleft between the PPXD and NBD2 is referred to as the clamp, and, depending on the position of the PPXD, it can be in an open (5), partially open (8), or closed form (10). The PPXD has been proposed to interact with preproteins (11)(12)(13)(14).…”
mentioning
confidence: 99%